Rising prevalence of multiple sclerosis worldwide: Insights from the Atlas of MS, third edition - Walton, Clare; King, Rachel; Rechtman, Lindsay; Kaye, Wendy; Leray, Emmanuelle; Marrie, Ruth Ann; Robertson, Neil; La Rocca, Nicholas; Uitdehaag, Bernard; van der Mei, Ingrid; Wallin, Mitchell; Helme, Anne; et al. (Multiple sclerosis, 2020)
High-quality epidemiologic data worldwide are needed to improve our understanding of disease risk, support health policy to meet the diverse needs of people with multiple sclerosis (MS) and support advocacy efforts. The Atlas of MS is an open-source global compendium of data regarding the epidemiology of MS and the availability of resources for people with MS reported at country, regional and global levels. Country representatives reported epidemiologic data and their sources via survey between September 2019 and March 2020, covering prevalence and incidence in males, females and children, and age and MS type at diagnosis. Regional analyses and comparisons with 2013 data were conducted. A total of 2.8 million people are estimated to live with MS worldwide (35.9 per 100,000 population). MS prevalence has increased in every world region since 2013 but gaps in prevalence estimates persist. The pooled incidence rate across 75 reporting countries is 2.1 per 100,000 persons/year, and the mean age of diagnosis is 32 years. Females are twice as likely to live with MS as males. The global prevalence of MS has risen since 2013, but good surveillance data is not universal. Action is needed by multiple stakeholders to close knowledge gaps.